Complications of blood donation reported to haemovigilance systems: analysis of eleven years of international surveillance. Issue 6 (5th December 2020) - Wiersum‐Osselton, Johanna C; Politis, Constantina; Richardson, Clive; Goto, Naoko; Grouzi, Elisavet; Marano, Giuseppe; Land, Kevin J
Abstract : Background and Objectives: The International Haemovigilance Network collects aggregate data on complications of blood donation from member haemovigilance systems (HVS). We analysed the data collected in 2006–2016 in order to learn from it and consider future improvements. Materials and Methods: National HVS entered annual data on donation complications and on annual whole blood and apheresis donations in the 'ISTARE' (International Surveillance of Transfusion Adverse Reactions and Events) online database. We calculated national and aggregate donation complication rates. Results: Twenty‐four HVS provided data for 138 country years (CY; median 7 CY, IQR 2–8), covering 155 M donations. The overall complication rate was 6·3/1000 donations and the median country rate 3·2/1000 (IQR 1·1–10·1). Overall and severe complication rates varied considerably between HVS. Vasovagal reactions (VVR) were most commonly reported: 4·6/1000 donations, median country rate 3·1/1000 donations (IQR 0·6–7·7). Rare complications included generalized allergic reaction (0·10/100 000) and major blood vessel injury (category available since 2015; 0·12/100 000). Eighteen HVS reported complications of whole blood donation (WBD) and apheresis separately (89 CY, 101·6 M WBD and 26·3 M apheresis donations). The median country VVR rate was 3·4/1000 WBD (IQR 1·0–9·1) and 1·5/1000 apheresis donations (1·0–4·2). Rates of venepuncture‐related complications tended to be higher for apheresis: the median country rate of reported haematomas was 0·39/1000 WBD (IQR 0·31–1·2) vs. 4·2/1000 apheresis donations (0·69–5·6). Conclusion: International reporting allows HVS to study rates of blood donation complications and capture information about very rare events. The present variability of reporting and severity assessment hampers comparisons between HVS and requires further work.